AKTIVITAS ANTIBAKTERI PROTEIN KAPANG Xylaria psidii KT30 TERHADAP Escherichia coli DAN Bacillus subtilis [Antibacterial Activity of Protein Fungus Xylaria psidii KT30 Escherichia coli and Bacillus subtilis] - Aris Munandar; A. Zaenal Mustopa; Kustiariyah Tarman; Tati Nurhayati (Jurnal Teknologi dan Industri Pangan, 2014)
Previous research shows that extracellular protein of an algicolous fungus Xylaria psidii KT30 inhibited Bacillus pumilus, Listeria sp., Salmonella typhi, Staphylacoccus aureus, and Pseudomonas sp. with an average clear zone diameter of 7 mm. To enhance the potent antibacterial activity of extracellular protein from Xylaria psidii KT30, the present research demonstrated fungal growth optimization and purification of its secreted extracellular protein. The fungal growth optimization was performed following NaCl concentration and harvest day variations. The protein was precipitated using ammonium sulphate at 60%-90% saturation range and was purified through gel chromatography filtrationusing Sephadex G-50, eluted with 30% aq methanol. The active fraction possesing antibacterial activity was then determined resulting supernatant, pellet, and protein fraction.The fungal was optimally obtained after 15 days cultivation using freshwater.The highest protein yield was 1.67%, resulted over 90% saturation. Fractions 11 and 12 were the most active against Escherichia coli dan Bacillus subtiliswith clear zone diameter of 8 mm.Three bands of those fractions were detected through SDS-PAGE analysis, revealing molecular weights of 23.42, 20.09, and 14.33 kDa.